Empirical investigation on loan loss provisions: a cross country analysis / Hasni Abdullah - Abdullah, Hasni (Institute of Graduate Studies, UiTM, 2016)
The present study examines the determinants of loan loss provisions with the presence of earnings management and capital management by commercial banks in the emerging and developed markets during the period of 2004 to 2012. Besides the main objective, there are external factors as well as the internal factors investigated in determining the loan loss provisions. This study focuses on the banking sectors that specify the commercial banks for the period of 2004 to 2012 in selected emerging and developed markets. In order to achieve the objectives of this study, Malaysia and Thailand are chosen to represent the emerging markets, while the developed markets are represented by Hong Kong and Japan. The empirical findings based on Pooled Ordinary Least Square (Pooled OLS) with Newey-West Standard Error for emerging markets and Fixed Effects (FE) with heteroscedasticity and autocorrelation for developed markets recommend that earnings management, gross domestic product and certain bank internal factors have a statistically significant impact on loan loss provisions…